Process optimization for the manufacture of Low-calorie yoghurt - Ghazal, Saniya; Rai, Dinesh Chandra; Rai, Saloni (Indian Journal of Dairy Science, 2022)
The present study was carried out to prepare low-calorie yoghurt by adding inulin @1, 2, and 3% in skim milk as well as in double toned milk, and the effect of inulin as a fat replacer on the quality of low-calorie yoghurt preparation was investigated and compared with control yoghurt made from whole milk. The sensory, and physicochemical characteristics were examined at 0, 7, and 14 days of storage period. Based on sensory evaluation, T4 (double toned milk + 1% inulin) was considered as best about flavor, color and appearance, body and texture, and overall acceptability scores were 8.30 ± 0.120, 8.50 ± 0.115, 7.96 ± 0.176, and 8.03 ± 0.058 respectively. It was found that total fat%, protein%, ash%, pH, acidity%, total solid%, carbohydrate%, and calorific value of T4 showed 1.50 ± 0.000, 4.13 ± 0.012, 1.032 ± 0.001, 4.50 ± 0.012, 0.984 ± 0.001, 12.40 ± 0.011, 5.74 ± 0.001, 52.98 ± 0.077 Kcal/100g. The cost of the low-calorie yoghurt based on raw ingredients per 100g was Rs. 21.87 Therefore, the production of low-calorie yoghurt was economical.